Outdoor air pollution exposure and inter-relation of global cognitive performance and emotional distress in older women. (15th February 2021) - Petkus, Andrew J.; Wang, Xinhui; Beavers, Daniel P.; Chui, Helena C.; Espeland, Mark A.; Gatz, Margaret; Gruenewald, Tara; Kaufman, Joel D.; Manson, JoAnn E.; Resnick, Susan M.; Stewart, James D.; Wellenius, Gregory A.; et al.
Abstract: The interrelationships among long-term ambient air pollution exposure, emotional distress and cognitive decline in older adulthood remain unclear. Long-term exposure may impact cognitive performance and subsequently impact emotional health. Conversely, exposure may initially be associated with emotional distress followed by declines in cognitive performance. Here we tested the inter-relationship between global cognitive ability, emotional distress, and exposure to PM2.5 (particulate matter with aerodynamic diameter <2.5 μm) and NO2 (nitrogen dioxide) in 6118 older women (aged 70.6 ± 3.8 years) from the Women's Health Initiative Memory Study. Annual exposure to PM2.5 (interquartile range [IQR] = 3.37 μg/m 3 ) and NO2 (IQR = 9.00 ppb) was estimated at the participant's residence using regionalized national universal kriging models and averaged over the 3-year period before the baseline assessment. Using structural equation mediation models, a latent factor capturing emotional distress was constructed using item-level data from the 6-item Center for Epidemiological Studies Depression Scale and the Short Form Health Survey Emotional Well-Being scale at baseline and one-year follow-up. Trajectories of global cognitive performance, assessed by the Modified-Mini Mental State Examination (3MS) annually up to 12 years, were estimated. All effects reported were adjusted for important confounders. Increases in PM2.5 (β = -0.144 per IQR; 95% CI = −0.261; −0.028) and NO2 (β = −0.157 per IQR; 95% CI = −0.291; −0.022) were associated with lower initial 3MS performance. Lower 3MS performance was associated with increased emotional distress (β = −0.008; 95% CI = −0.015; −0.002) over the subsequent year. Significant indirect effect of both exposures on increases in emotional distress mediated by exposure effects on worse global cognitive performance were present. No statistically significant indirect associations were found between exposures and 3MS trajectories putatively mediated by baseline emotional distress. Our study findings support cognitive aging processes as a mediator of the association between PM2.5 and NO2 exposure and emotional distress in later-life. Graphical abstract: Image 1 Highlights: We examined exposure to air pollution with emotional and cognitive health. Women with higher PM2.5 and NO2 exposure had worse baseline cognitive performance. Women with worse cognitive performance had increases in emotional distress. Cognitive ability mediated pollutant effects on increases in emotional distress.